Early category and concept development : making sense of the blooming, buzzing confusion - Rakison, David H., 1969-; Oakes, Lisa M., 1963- (OUP E-Books., 2003)
This text brings together contemporary findings and theories about the origins and early development of categorization and conceptual abilities. Despite advances in our understanding of this area, a number of hotly debated issues remain at the centre of the controversy over categorization.